2003
DOI: 10.1074/jbc.m303349200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of YopT Effects on Rho GTPases in Yersinia enterocolitica-infected Cells

Abstract: Pathogenic yersiniae employ a type III secretion system for translocating up to six effector proteins (Yersinia outer proteins (Yops)) into eukaryotic target cells. YopT is a cysteine protease that was shown to remove the C-terminal isoprenoid group of RhoA, Rac, and CDC42Hs. Here we characterized the cell biological and biochemical activities of YopT in cells infected with pathogenic Yersinia enterocolitica. Bacterially injected YopT located to cell membranes from which it released RhoA but not Rac or CDC42Hs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…It should be mentioned that, although the effect of YopE and YopT on caspase-1 activation was comparable upon overexpression in HEK293T cells and mediated by their effect on Rho GTPases (as shown by the use of specific YopE and YopT mutants), the effect of YopE was much more pronounced in the case of Yersinia infected macrophages. Although the underlying mechanism of Rho GTPase inhibition by YopE and YopT is different, they both have been shown to inhibit Rac1, RhoA, and Cdc42 in vitro or upon overexpression (4,5,28,37). However, in Yersinia infected macrophages, YopE and YopT have been shown to specifically inhibit Rac1 and RhoA, respectively (28,37).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It should be mentioned that, although the effect of YopE and YopT on caspase-1 activation was comparable upon overexpression in HEK293T cells and mediated by their effect on Rho GTPases (as shown by the use of specific YopE and YopT mutants), the effect of YopE was much more pronounced in the case of Yersinia infected macrophages. Although the underlying mechanism of Rho GTPase inhibition by YopE and YopT is different, they both have been shown to inhibit Rac1, RhoA, and Cdc42 in vitro or upon overexpression (4,5,28,37). However, in Yersinia infected macrophages, YopE and YopT have been shown to specifically inhibit Rac1 and RhoA, respectively (28,37).…”
Section: Discussionmentioning
confidence: 95%
“…Although the underlying mechanism of Rho GTPase inhibition by YopE and YopT is different, they both have been shown to inhibit Rac1, RhoA, and Cdc42 in vitro or upon overexpression (4,5,28,37). However, in Yersinia infected macrophages, YopE and YopT have been shown to specifically inhibit Rac1 and RhoA, respectively (28,37). The latter observation together with our own data showing that IL-1␤ release from YopPE Ϫ -infected macrophages is much higher compared with the release from YopPT Ϫ -infected cells point to a major role for Rac1 in caspase-1 activation and the proteolytic maturation of proIL-1␤ in Yersinia infected macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…YopT, a cysteine protease, inactivates RhoA by cleavage adjacent to a prenylated cysteine located near the carboxy terminus, resulting in membrane release and cytoplasmic redistribution of RhoA (60). However, some studies also showed some effect of YopT on Rac and Cdc42 in biochemical assays performed in vitro (61), but after infection of living cells, YopT seems to act mainly on RhoA (2).…”
mentioning
confidence: 99%
“…94 In vivo, the preferred target of YopT is RhoA. 95 YopT is the prototype of a new protein fold subfamily of proteases, which among others encompasses toxin B from E. coli or the avirulent protease AvrPphB of the plant pathogen Pseudomonas syringae. 96 This classification was based on predictions and homology analysis, although the actual 3D-structure of YopT has not been resolved yet.…”
Section: Structure and Functionmentioning
confidence: 99%